K-Ar fault-gouge dating in the Lower Buller gorge constrains the formation of the Paparoa Trough, West Coast, New Zealand. Issue 1 (2nd January 2021) - Ring, Uwe; Uysal, Ibrahim Tonguc; Tong, Kui; Todd, Andrew
ABSTRACT: K-Ar dating of fault gouge from the intersection of the WNW-striking Ohika Detachment of the Paparoa Metamorphic Core Complex and a NNE-striking high-angle normal fault (Ohikaiti Fault) yielded an age of 103 ± 3.5 Ma (1σ uncertainty) for metamorphic white mica and an age of 35.2 ± 2.3 Ma for fault-gouge formation. The K-Ar four-point isochron is well defined and the upper-intercept age of 103 ± 3.5 Ma is inferred to reflect growth of metamorphic white mica in the footwall of the Paparoa Metamorphic Core Complex. We relate the fault gouge at the Ohikaiti Fault to the formation of the Paparoa Trough in the latest Eocene and the deposition of the Rapahoe Group. The NNE-striking Ohikaiti Fault either reactivated a favourably oriented segment of the Ohika Detachment or cut the detachment and displaced it when the Paparoa Trough formed. We discuss a model of relatively modest deformation in the Paparoa Trough as part of the Challenger Rift System because the northern West Coast region was close to the pole of plate rotation in the late Eocene and Oligocene.